Evaluation of students’ perceptions of game-based mathematics classroom using fuzzy conjoint analysis / Azimah Suparlan …[et al.] - Suparlan, Azimah; Shohaimay, Fairuz; Haron, Nur Fatihah; Zainal Abidin, Syazwani; Dasman, Anisah; Mokhtar, Mazura (Universiti Teknologi MARA Cawangan Pahang, 2019)
Teaching mathematics can be challenging with students of weak mathematical background. Most of these students are uninterested and perform poorly in written assessments. Game-based learning is one of the approaches to increase students' motivation and engagement in the classroom. This study aims to investigate the students' perceptions of game-based mathematics classrooms by fuzzy set conjoint analysis. The study involves a survey collected from 83 undergraduate students of Faculty of Computer and Mathematical Sciences (FSKM), Raub Campus. The survey consists of 16 items of the students' perceptions of incorporating mathematical board game in the classroom. Eight items area bout students' involvement during the game, and the other eight items area bout cooperation during the game. A seven-point Likert scale was used to collect students' responses for each of the items. Then, the fuzzy set was used to represent the Likert scale, and the scores of students' perceptions were the degree of similarities. The findings showed that the items related to students' involvement were recorded at the highest degree of similarity at 0.52 with the level of 'Agree' that students' ideas and suggestions were used during the discussions in the game. Likewise, the items related to cooperation obtained the highest degree of similarity at 0.518, also with the level of 'Agree' that the students cooperate with other students during the activity. This study found students generally had a positive perception towards game-based mathematics classroom